Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Bilateral Di RSO. Prof. Dr. R Soeharso - Rofiatun, Atika Puji, Dwi Kurniawati, SSt. Ft, M. Kes (2015)
Background: Carpal Tunnel Syndrome (CTS) is one of disturbance on the arm due to the narrowing of the carpal tunnel, either due to edema of the fascia on the tunnel or due to abnormalities in the small bones of the hand resulting in suppression of the wrist median nerve. Carpal Tunnel S yndrome interpreted as a weakness of the hands that ache in the median nerve distribution area. Problem physiotherapy obtained is the presence and motion tenderness and pain in the hands of patients. A decrease in muscle strength of the patient's right and left hands. Methods: The method in handling such cases using Infra Red (IR), ultrasound (US) and Therapeutic Exercise, which was evaluated by the method of measurement if pain (VAS), measurement of muscle strength (MMT). Objective: the above method to determine the benefits of therapy with IR modalities, US and exercise therapy to reduce pain, increase muscle strength. Results: after 6 times the therapy showed a decrease in pain, an increase in MMT. Conclusion: IR, US and Therapeutic Exercise can reduce pain in such cases and can increase muscle strength.